An Examination of Work–Family Conflict in NCAA Division III and NAIA Sports Information Professionals - Laura M. Hatfield; Jeffrey T. Johnson (Journal of Applied Sports Management, 2013)
Work–family conflict (WFC) is defined as “the discord that arises when the time devoted to or time spent fulfilling professional responsibilities interferes with or limits the amount of time available to perform family-related responsibilities” (Netemeyer, McMurrian, & Boles, 1996). A successful career in sports information requires long, demanding hours that can make finding balance between work and family difficult. The purpose of this study was to determine if NCAA Division III and NAIA sports information professionals (SIDs) experience WFC and to examine the impact of WFC on the related theories of life satisfaction (LS), job satisfaction (JS), job burnout (JB), and career commitment (CC). Results from the online survey indicated these professionals experience WFC. Correlation and regression analyses revealed significant statistical relationships between each scale and indicated WFC could successfully predict variations in LS, JS, JB, and CC.
Keywords: Sports information; media relations; work–family conflict